جهود الجزائر لتحقيق التعاون الدولي في مجال مكافحة تهريب المهاجرين - بن مشري, عبد الحليم (revue mofakir, 2018)
Smuggling of migrants is considered as one of the most spreading activities of organized crime networks, in view of the increased statistics annually, and the extension of criminal networks involved in the smuggling of migrants, it became necessary to the states, intervention for fighting all sorts of organized crime, in the form of an international cooperation, at time when it’s difficult for any country to fight these organized criminal groups alone. This paper aims at highlighting this point, through focusing on the mechanisms used by Algeria in international cooperation framework to fight smuggling migrants.